1978
DOI: 10.1159/000181466
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII Procoagulant Activity in Children with Nephrotic Syndrome and Post-Streptococcal Glomerulonephritis

Abstract: Plasma factor VIII procoagulant activity has been shown to be significantly elevated in 32 children with the nephrotic syndrome. This increase is more marked in those with obvious glomerular lesions on histology than in patients with minimal change nephropathy. Fluctuations in factor VIII levels corresponded to changes in the clinical condition of the nephrotic syndrome. In 28 children with post-streptococcal glomerulonephritis, 4 patients with the highest factor VIII levels recovered between 7 and 60 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition, disturbances of liver protein syn theses are present in NS and seem dependent, at least partly, on hypoalbuminemia. While synthesis of albumin may be normal or only slightly increased [33,34], that of fibrinogen and transferrin is markedly increased [14,35], In nephrotic rats with Heymann nephritis, immunocytochemical methods disclosed an increased number of hepatocytes containing fibrinogen [36], suggesting that enhanced liver synthesis, in the absence of urinary loss, accounted for hyperfibrinogenemia; in contrast there were no changes in the number of cells containing albu min or AT III, and therefore no compensation for uri nary loss of both proteins [36], Most studies in humans are in agreement with these results and have shown cor relations between the intensity of coagulation disorders and the intensity of albuminuria and hypoalbuminemia [1,4,5,7,8,15,23], as already mentioned for AT III disorders.…”
Section: Abnormalities Of Coagulation and Fibrinolysis Factors In Sysmentioning
confidence: 89%
“…In addition, disturbances of liver protein syn theses are present in NS and seem dependent, at least partly, on hypoalbuminemia. While synthesis of albumin may be normal or only slightly increased [33,34], that of fibrinogen and transferrin is markedly increased [14,35], In nephrotic rats with Heymann nephritis, immunocytochemical methods disclosed an increased number of hepatocytes containing fibrinogen [36], suggesting that enhanced liver synthesis, in the absence of urinary loss, accounted for hyperfibrinogenemia; in contrast there were no changes in the number of cells containing albu min or AT III, and therefore no compensation for uri nary loss of both proteins [36], Most studies in humans are in agreement with these results and have shown cor relations between the intensity of coagulation disorders and the intensity of albuminuria and hypoalbuminemia [1,4,5,7,8,15,23], as already mentioned for AT III disorders.…”
Section: Abnormalities Of Coagulation and Fibrinolysis Factors In Sysmentioning
confidence: 89%
“…Of several series screening hemostatic protein abnormalities in nephrotic syndrome patients, Kanfer et al (9) described elevated levels of factors V, VIII and fibrinogen and thrombocytosis. High factor VIII activities may be prognostically useful in some patients urith renal diseases (35) and are accompanied, as in the present series, by elevations of factor Vlll-related antigen (von Willebrand factor) (36,37). Except for one case (38), increased clotting activities of factors VII and X have also been noted in nephrotic slmdrome patients (11).,Although high levels of these factors are often associated with "h54tercoagulable" states, a lack of correlation with thrombosis is noteworthy; as in other clinical situations, elevations presumably reflect changes associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorheology is altered by multiple triggers such as blood hypercoagulability, hyper viscosity, platelet hyperaggregability, a defective deformability of red blood cells, hyperaggregation of red blood cells in the presence of low fluid shear stress or hypoperfu sion, an increase in blood elements, and vessel wall inter action due to the increased expression of adhesion mole cules. Therefore, a progressive reduction in blood and its ischemic consequences are due to a deficiency in both the quality and quantity of blood [69,70,[90][91][92][93][94][95][96][97],…”
mentioning
confidence: 99%